Resource use efficiency of milk production across different herd sizes of buffaloes and crossbred cows in Middle Gujarat - Satashia, Maitri; Pundir, RS; Darji, VB (Indian Journal of Dairy Science, 2021)
The most important objective of any production unit is to co-ordinate and utilize the various resources of production in such a manner that they yield the highest net returns. Â As farmers are shifting from low input-low output to high input-high output and traditional and subsistence to commercial dairy farming, this study assesses the impact of resources being used optimally through herd size categories by the dairy farmers for buffaloes and crossbred cows in the Middle Gujarat region. The resource use efficiency analysis helps the dairy farmers in taking appropriate decisions regarding resource allocation without using additional resources for enhancing their income. The findings show that on an average, the costs of human labour, green fodder and concentrates had significant influence on milk yield for buffalo milk production while costs of human labour, green fodder, concentrates and veterinary and medical charges had significant influence on milk yield for crossbred cow milk production implying that one per cent increase in the use of these inputs can led to increase in the gross returns from milk. Milk production for buffaloes was in decreasing returns to scale while on an overall basis, milk production for crossbred cows was increasing returns to scale. Further, the difference between MVP and its acquisition unit price for human labour in small category, green fodder in overall category and dry fodder in marginal category in buffalo milk production and price for human labour in medium and overall category and green fodder in large category in crossbred cow milk production were found positive and significant indicating that the dairy farmers have an opportunity to increase their profit by using more of these inputs on their farms. Thus, the study concluded that only in crossbred cows, milk production was size neutral.